The Constitution and American racism: setting a course for lasting injustice - Madden, David P. (McFarland & Company, Inc., Publishers, 2021)
"The security the Southern states want..." -- "The peculiar institution" -- The law of slavery -- State's rights as revisionist history -- "The Constitution is color blind" -- Tyranny of the Republic -- The power vested in the President -- Civil rights -- Democracy is government "by and for the people".